Race, Ethnicity, and Trial Avoidance: A Multilevel Analysis - Lee, Jacqueline G. (Criminal justice policy review, 2020)
Minority criminal defendants are more likely than White defendants to exercise their right to trial, which is concerning given that research also consistently finds trial sentences to be harsher than those obtained via pleas. However, guilty pleas are not the only disposition available for avoiding a trial; pretrial diversions and case dismissals also serve as mechanisms for trial avoidance. Using hierarchical linear modeling, we find that Black criminal defendants are more likely than Whites to go to trial rather than receive other case disposition. Relationships for Hispanic defendants are less consistent. Fewer county-level effects emerge than expected, providing little to no support for racial threat theory. Results suggest that Black defendants are less often able or willing to avoid a trial, a finding which highlights and perhaps helps to explain racial disparities in final sentencing outcomes.